Primers Designed For Amplifying TCF7L2 Gen - S. Syamsurizal; Hengki Saputra; Dwi Hilda Putri; Elsa Badriyya (Biota, 2020)
Diabetes Mellitus (DM) is a disease characterized by high glucose levels because of the lack of insulin hormone in the body. Prevalence of Type-2 Diabetes Mellitus is associated with the variant of the TCF7L2 gene polymorphism, or SNP. The purpose of this study was to construct a specific primer to amplify the TCF7L2 gene fragment and their capabilities to detect the targeted area. This research was a descriptive study that design the primers using Geneious software version 5.4.7. The study was conducted at the Laboratory of Genetics and Biotechnology FMIPA Universitas Negeri Padang. Based on this research, a 10qF forward primer (NG_012631.1) and 10qR reverse primers (NG_012631.1) has successfully designed. The primers can amplify the targeted area of the TCF7L2 gene with 1208 bp length. The amplified gene region has many variants that are strictly related to the appearance of Type 2 Diabetes Mellitus.